Determinants of Fathers’ Attitude Toward Breastfeeding Support: DETERMINAN AYAH ASI - Wahyu Pujiastuti (Midwifery and Nursing Research, 2026)
Background : Minimum service standards are stated to be fulfilled if breastfeeding coverage reaches more than 80%. The husband is the main support system in the successful practice of exclusive breastfeeding through the provision of informational, instrumental, emotional and assessment support. To be able to provide support is influenced by several factors. The purpose of this study was to find out what factors were the determinants of the implementation of breastfeeding fathers. Methods : This research uses observational analytic research method with cross sectional design and spearman rank statistical analysis. The population of t his study is the husband of pregnant women Third Trimester in the City of Magelang. The sampling technique used purposive sampling technique. Data was obtained by distributing questionnaires via google form. Results : The results showed that there was no relationship between the level of education and the attitude of being a breastfeeding father, p value 0.392 (>α 0.005), there was no relationship between the level of income and the attitude of being a breastfeeding father, p value 1,000 (>α 0.005) and there was a relationship between the level of knowledge with the attitude of being a breastfeeding father, p value 0.000 (<α0.005). Conclusion : Father's level of knowledge about breastfeeding fathers must be increased in order to support his wife to be able to exclusively breastfeed. Midwives can provide assistance to husbands to increase knowledge so that more husbands become breastfeeding fathers.